2013
DOI: 10.1287/inte.2013.0708
|View full text |Cite
|
Sign up to set email alerts
|

The Ombudsman: The “Wicked” Environment of CEO Pay

Abstract: We applaud Jacquart and Armstrong’s systematic, evidence-based review of the contentious issue of CEO remuneration. We augment their analysis. First, we highlight the lack of demonstrated validity of unaided expert judgment to set CEO remuneration. The settings in which such judgments are made do not facilitate learning through experience and are subject to many biases. In particular, we briefly describe our empirical study that demonstrates illusory correlation in the form of a relationship between golfing ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…When cause‐effect relationships are difficult to ascertain, managers may create beliefs about interdependencies that actually do not exist, falling prey to “apophenia” (Conrad, ) or “patternicity” (Shermer, ), the inclination of seeing patterns in meaningless data. Managers may perceive “illusory correlations” (Hogarth and Kolev, ), that is, they perceive correlations among unrelated factors. Experimental studies by psychologists and experimental economists have documented the prevalence of errors of “covariation assessment” (e.g., Einhorn and Hogarth, ); people may fail to understand covariation for even the simplest 2 × 2 contingency tables.…”
Section: Existing Literaturementioning
confidence: 99%
“…When cause‐effect relationships are difficult to ascertain, managers may create beliefs about interdependencies that actually do not exist, falling prey to “apophenia” (Conrad, ) or “patternicity” (Shermer, ), the inclination of seeing patterns in meaningless data. Managers may perceive “illusory correlations” (Hogarth and Kolev, ), that is, they perceive correlations among unrelated factors. Experimental studies by psychologists and experimental economists have documented the prevalence of errors of “covariation assessment” (e.g., Einhorn and Hogarth, ); people may fail to understand covariation for even the simplest 2 × 2 contingency tables.…”
Section: Existing Literaturementioning
confidence: 99%
“…According to Dawes (1994), these two attributes are positively correlated in the real world. Shanteau and Thomas (2001) labeled positively-correlated environments as “friendly,” since it is easy to maximize decision outcomes (for a follow-up to this idea, see Hogarth & Kolev, 2013). By selecting a job candidate with high test scores, you also get high grades and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…He presents evidence that executive compensation-in terms of overall wealth rather than annual pay-is related to firms' performance. In contrast, Hogarth and Kolev (2013) suggest that attention should be given to how current pay affects future performance. Answering this question with nonexperimental data, they found that total compensation was negatively correlated to future performance.…”
Section: How Should Performance Be Assessed?mentioning
confidence: 99%